Assessing the force-velocity characteristics of the leg extensors in well-trained athletes: The incremental load power profile - Sheppard, J. M.; Cormack, S.; Taylor, K.-L.; McGuigan, M. R.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this research project was to evaluate the methodology of an iso-inertial force-velocity assessment utilizing a range of loads and a group of high-performance athletes. A total of 26 subjects (19.8 +/- 2.6 years, 196.3 +/- 9.6 cm, 88.6 +/- 8.9 kg) participated in this study. Interday reliability of various force-time measures obtained during the performance of countermovement jumps with a range of loads was examined, followed by a validity assessment of the various measures' ability to discriminate among performance levels, while the ability of the test protocol to detect training-induced changes was assessed by comparing results before and after an intensive 12-week training period. Force and velocity variables were observed to be reliable (intraclass correlation coefficient 0.74-0.99). Large effect size statistic (ES > 0.50) differences among player groups were observed for peak power (1.36-2.25), relative peak power (1.57-2.42), and peak force (0.74-0.95). Significant (p < 0.05) and large (ES > 0.50) improvements were observed in the kinetic values after the intensive training period. The results of this study indicate that the incremental load power profile is an acceptably reliable, valid, and sensitive method of assessing force and power capabilities of the leg extensors in high-performance and elite volleyball players.